2020
DOI: 10.1007/s10519-020-10023-x
|View full text |Cite
|
Sign up to set email alerts
|

The Heritability of Type D Personality by an Extended Twin-Pedigree Analysis in the Netherlands Twin Register

Abstract: Type D (Distressed) personality combines negative affectivity (NA) and social inhibition (SI) and is associated with an increased risk of cardiovascular disease. We aimed to (1) validate a new proxy based on the Achenbach System of Empirically Based Assessment (ASEBA) for Type D personality and its NA and SI subcomponents and (2) estimate the heritability of the Type D proxy in an extended twin-pedigree design in the Netherlands Twin Register (NTR). Proxies for the dichotomous Type D classification, and contin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…Also of interest is that few twin and family studies of MDD report estimates of non-additive effects (D), whereas we find roughly equal additive and non-additive genetic contributions to the broad-sense heritability (making up 18.9% and 14.6% of total phenotypic variance, respectively). Similar increases in non-additive genetic effects have been reported in extended twin pedigree designs for other traits (e.g., [40,57,58]), and may result from increases in statistical power or the ability to model additional variance components. We note that the inclusion of non-twin family relations introduces age differences within relative pairs, which might mimic non-additive effects when, for example, age differences result in reduced resemblance in parent-offspring pairs, but not in DZ twin or sibling pairs (Table 1).…”
Section: Discussionmentioning
confidence: 54%
“…Also of interest is that few twin and family studies of MDD report estimates of non-additive effects (D), whereas we find roughly equal additive and non-additive genetic contributions to the broad-sense heritability (making up 18.9% and 14.6% of total phenotypic variance, respectively). Similar increases in non-additive genetic effects have been reported in extended twin pedigree designs for other traits (e.g., [40,57,58]), and may result from increases in statistical power or the ability to model additional variance components. We note that the inclusion of non-twin family relations introduces age differences within relative pairs, which might mimic non-additive effects when, for example, age differences result in reduced resemblance in parent-offspring pairs, but not in DZ twin or sibling pairs (Table 1).…”
Section: Discussionmentioning
confidence: 54%
“…Social inhibition was assessed by the social inhibition subscale of the recently validated ASEBA-based proxy questionnaire for components of type D personality using the Netherlands Twin Registry adult twin-family dataset (Li-Gao et al, 2021). Identical items (“ I have trouble making or keeping friends,” “ I would rather be alone than with others ,” “ I am secretive or keep things to myself ,” “ I am too shy or timid, ” “ I keep from getting involved with others, ” and “ Others do not like me ”) were derived from the adult self-report (ASR) and the Young Adult self-report form (YASR; Li-Gao et al, 2021). ASR/YASR is well-validated instrument, which is part of the Achenbach System of Empirically Based Assessment (ASEBA) taxonomy (Achenbach et al, 2017), and consists of items assessing adaptive functioning and problems.…”
Section: Methodsmentioning
confidence: 99%
“…The scores on the SI scales range between 0 and 12, with a higher score indicating greater social inhibition. The previous study on the adult sample from the Netherlands Twin Register showed that the SI scale (based on ASR) was valid and had good internal consistency (Li-Gao et al, 2021). We additionally assessed internal consistency of the SI scale at the younger ages (based on YASR) by calculating McDonald’s omega (Hayes & Coutts, 2020).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation